Cooking has the potential to decrease the antitumor effect of fresh Betong watercress. Issue 4 (24th January 2019) - Aksornthong, Chunhajan; Prutipanlai, Sathaporn; Ruangrut, Pritsana; Janchawee, Benjamas
Abstract: Betong watercress ( Nasturtium officinale R.Br.) contains phenethyl isothiocyanate (PEITC), derived from myrosinase‐mediated hydrolysis of glucosinolates. Effects of fresh and cooked Betong watercress (FBW & CBW) on N ‐demethylation and C‐8‐hydroxylation of caffeine (CF) in rats were investigated. Wistar rats received a single dose of CF before and after pretreatments with a single or five‐day administration of PEITC, FBW, and CBW dry powders. Plasma CF metabolic ratios (CMRs) were compared between before and after pretreatments. Single pretreatment with PEITC, FBW, but not CBW, significantly decreased CMRs. Five‐day pretreatment with PEITC, FBW, and CBW significantly decreased CMRs. The decreases in CMRs after multiple doses of PEITC, FBW, and CBW were significantly higher than after a single dose. The decrease in CMRs caused by CBW was significantly lower than those by FBW, both single‐ and multiple doses. Cooking decreases the activity of FBW in inhibition of CYP1A2 mediating CF metabolism. Practical applications: PEITC and fresh watercress possess chemoprotective effects due to the inhibitory activity of PEITC on cytochrome P450s mediated bioactivation of carcinogens. Several clinical trials of the therapeutic uses of PEITC for cancer and other diseases are still in the pipeline. Betong watercress is a common ingredient in hot soup and stir‐fried Thai recipes. Cooking heat inactivates plant myrosinase involving the production of PEITC. Consumption of watercress in cooked form may contribute less chemoprotective benefit. More appropriate preparation to deliver PEITC is needed to be evaluated.